2018
DOI: 10.1055/s-0038-1666835
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Postoperative Pain and Recovery between Single-Port and Two-Port Thoracoscopic Lobectomy for Lung Cancer

Abstract: Compared with the multiport approach, SP VATS lobectomy might reduce postoperative pain and lead to faster recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…Some of our included studies did not control the same surgeon to perform these two procedures, which would bring potential bias to the results of our study. [7,20,21,23,26] Our meta-analysis showed a high heterogeneity in the comparative outcomes (except conversion rates and number of resected lymph nodes). Several included studies mentioned the learning curve for U-VATS, and it might cause high heterogeneity.…”
Section: Discussionmentioning
confidence: 82%
“…Some of our included studies did not control the same surgeon to perform these two procedures, which would bring potential bias to the results of our study. [7,20,21,23,26] Our meta-analysis showed a high heterogeneity in the comparative outcomes (except conversion rates and number of resected lymph nodes). Several included studies mentioned the learning curve for U-VATS, and it might cause high heterogeneity.…”
Section: Discussionmentioning
confidence: 82%
“…After 1:1 matching, 110 patients remained for analysis, baseline demographic and clinical variables were comparable between the two groups (Table 1). In tubeless group, the mean diameter of the lesions was 9.8 mm (7)(8)(9)(10)(11)(12)(13)(14). The postoperative VAS score was signi cantly lower in tubeless group than in drainage group in postoperative day 1 and 3.…”
Section: Resultsmentioning
confidence: 90%
“…In tubeless group, the mean diameter of the lesions was 9.8 mm (7)(8)(9)(10)(11)(12)(13)(14). The locations of PPN included right upper lobe, right lower lobe, left upper lobe and left lower lobe.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that patients who underwent non-intubated surgery correlated with shorter postoperative hospital stays and postoperative fasting time, they also exhibited a trend toward lower cardiovascular complication rates (1.45% vs 2.69%) and respiratory complication rates (8.23% vs 11.18%) (8,9) . Compared with multiportal VATS, uniportal VATS might reduce post-operation pain and lead to faster recovery (10) . Uni-portal VATS only invades a single intercostal region, thoracic muscles could also be spared, leading to less intercostal nerve disorder and less postoperative pain (11) .…”
Section: Discussionmentioning
confidence: 99%